Early outcomes from a randomized, controlled trial of supervised exercise, angioplasty, and combined therapy in intermittent claudication - Mazari, Fayyaz Ali Khan; Gulati, Sumit M.; Abdul Rahman, Mohd Norhisham Azmi; Lee, H L; Mehta, Tapan Anil; McCollum, Peter Thomas; Chetter, Ian Clifford (Elsevier, 2010)
BACKGROUND: To compare angioplasty (PTA), supervised exercise (SEP) and PTA + SEP in the treatment of intermittent claudication (IC) due to femoropopliteal disease. METHODS: Over a 6-year period, 178 patients (108 men; median age, 70 years) with femoropopliteal lesions suitable for angioplasty were randomized to PTA, SEP, or PTA + SEP. Patients were assessed prior to and at 1 and 3 months post treatment. ISCVS outcome criteria (ankle pressures, treadmill walking distances) and quality of life (QoL) questionnaires (SF-36 and VascuQoL) were analyzed. RESULTS: All groups were well matched at baseline. Twenty-one patients withdrew. Results are as follows: Intragroup analysis: All groups demonstrated significant clinical and QoL improvements (Friedman test, p < 0.05). SEP (60 patients, 8 withdrew)-62.7% of patients (n = 32) improved following treatment [20 mild, 9 moderate, 3 marked], 27.4% (n = 14) demonstrated no improvement, and 9.8% (n = 5) deteriorated. PTA (60 patients, 3 withdrew)-66.6% patients (n = 38) improved following treatment [19 mild, 10 moderate, 9 marked], 22.8% (n = 13) demonstrated no improvement, and 10.5% (n = 6) deteriorated. PTA + SEP (58 patients, 10 withdrew)-81.6% of patients (n = 40) improved following treatment [10 mild, 17 moderate, 3 marked], 14.2% (n = 7) demonstrated no improvement, and 4.0% (n = 2) deteriorated. Intergroup analysis: PTA + SEP produce a much greater improvement in clinical outcome measures than PTA or SEP alone, but there was no significant QoL advantage (Kruskal-Wallis test, p > 0.05). CONCLUSION: SEP should be the primary treatment for the patients with claudication and PTA should be supplemented by an SEP.